How effective is acupuncture in treating hot flashes in breast cancer patients? A systematic review and meta-analysis - Zhang, Genlan; Gao, Cui; Guo, Zining; Zhao, Wenrui; Xu, Xufang; Wen, Huaneng; Li, Yaoxuan; Lin, Run; Xu, Nenggui; Cui, Shaoyang (Frontiers in Oncology, 2025)
BackgroundAlthough acupuncture is recommended for managing breast cancer-related hot flashes, the level of evidence is limited. With the updating of randomized controlled trials, it is necessary to reassess its efficacy.ObjectiveTo assess the effectiveness of acupuncture in the treatment of hot flashes in patients with breast cancer.MethodsUp to March 2024, we retrieved data from nine databases and used Stata software (version 14.0, version 17.0) and RevMan software (version 5.3) to conduct a meta-analysis. The Cochrane Collaboration’s risk of bias assessment tool was used for methodological assessment of the risk of bias, and the GRADEpro GDT online assessment tool was used for evidence evaluation.ResultsIn total, 11 randomized controlled trials (RCTs) involved 963 participants were included in the meta-analysis. The result of risk of bias revealed that the included RCTs exhibited a high risk of bias, primarily attributable to deficiencies in randomization and blinding methods. The results of primary meta-analysis indicated that acupuncture can improved the hot flash symptom scale score (SMD, -0.54; 95% CI, -0.83 to -0.24; P < 0.05). However, acupuncture does not reduce the frequency of hot flashes(SMD, -0.20; 95% CI, -0.75 to 0.36; P = 0.48). Further subgroup analyses, including the type of control group and the duration of needle retention, etc. showed different results, highlighting the necessity for further research. Sensitivity analysis confirmed the reliability of these finding. In addition, due to various issues, the level of evidence is low.ConclusionsAlthough acupuncture treatment for hot flashes in breast cancer shows potential, the evidence for the efficacy of acupuncture is still lacking due to various factors such as bias risk and significant differences between studies, and more high-quality RCTs are needed to confirm the efficacy of acupuncture.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024531542.